Adsorption Behaviors of Cobalt on the Graphite and SiC Surface: A First-Principles Study - Wenyi Wang; Chuan Li; Jianzhu Cao; Chao Fang (Science and Technology of Nuclear Installations)
Graphite and silicon carbide (SiC) are important materials of fuel elements in High Temperature Reactor-Pebble-bed Modules (HTR-PM) and it is essential to analyze the source term about the radioactive products adsorbed on graphite and SiC surface in HTR-PM. In this article, the adsorption behaviors of activation product Cobalt (Co) on graphite and SiC surface have been studied with the first-principle calculation, including the adsorption energy, charge density difference, density of states, and adsorption ratios. It shows that the adsorption behaviors of Co on graphite and SiC both belong to chemisorption, with an adsorption energy 2.971 eV located at the Hollow site and 6.677 eV located at the hcp-Hollow site, respectively. Combining the charge density difference and density of states, it indicates that the interaction of Co-SiC system is stronger than Co-graphite system. Furthermore, the variation of adsorption ratios of Co on different substrate is obtained by a model of grand canonical ensemble, and it is found that when the temperature is close to 650 K and 1700 K for graphite surface and SiC surface, respectively, the Co adatom on the substrate will desorb dramatically. These results show that SiC layer in fuel element could obstruct the diffusion of Co effectively in normal and accidental operation conditions, but the graphite may become a carrier of Co radioactivity nuclide in the primary circuit of HTR-PM.